PROBLEMATIKA PUTUSAN MAHKAMAH KONSTITUSI NOMOR: 46/PUU-VIII/2010 TENTANG STATUS ANAK DI LUAR PERKAWINAN - Fira Mubayyinah (Al Hikmah: Jurnal Studi Keislaman, 2014)
That the decision of the Constitutional Court Number 46 / PUU-VII / 2010 regarding the judicial review of Law No. 1 of 1974 on Marriage contains the values of progressivism and would likely result in many possible issues in the future. Such values are contained in the legal interpretations made by the judges of the Constitutional Court in making a decision on the petition for the marriage law. The Constitutional Court did not simply decide it through positive law considerations, but through living laws in the community and legal norms even legal principles in order to create justice for the position of children born outside of marriage. The progressivism adopted by the Constitutional Court in its ruling on judicial review of Article 43 paragraph (1) Marriage Law No. 1 / 1974 results in the implications that drew criticism from the public. But the decision was the starting point in the protection of children born outside of marriage to have equal rights as other children. In the Constitutional Court's decision, the child will get a recognition in so far as he /she tries to prove it. The implication in this case is that there must be affirmative recognition of children out outside of marriage in the population administration. But the domino effect will continue with other children rights consequences when the recognition is applied. For example, the rights of inheritance and the ones of fulfilling the well-being of the child. For that reason, progressivism carried out by the Constitutional Court which is a form of protection for children born outside of marriage is still in need of regulations and restrictions on the implementation of the regulations.